2017
DOI: 10.3906/vet-1604-94
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four ultrasonographic approaches for the diagnosis ofacquired reticular diaphragmatic hernia in Bovidae

Abstract: The aim of this study was to look at four ultrasonographic approaches that diagnose acquired reticular diaphragmatic hernia (RDH) using either left or right caudal thoracic approaches (4th/5th intercostal space) and compare them to those made more cranially (1st/2nd intercostal space). Each sonographic observation was made in 27 unsedated, standing animals (22 buffaloes and 5 cattle) that were surgically confirmed for RDH. Using the right caudal thoracic approach, the herniated reticulum was seen as medial to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
4
6
0
Order By: Relevance
“…Although no reticular motility within the chest was observed, visualization of the reticulum adjacent to the heart and lung was a determining finding for the diagnosis of reticular diaphragmatic hernia. These findings were similar to those observed in other studies (Abdelaal et al 2014, Kumar et al 2017.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although no reticular motility within the chest was observed, visualization of the reticulum adjacent to the heart and lung was a determining finding for the diagnosis of reticular diaphragmatic hernia. These findings were similar to those observed in other studies (Abdelaal et al 2014, Kumar et al 2017.…”
Section: Discussionsupporting
confidence: 93%
“…There are no studies in the literature comparing the ultrasound diagnosis of diaphragmatic reticular hernia with necropsy images in cattle, thus, this is the first study to confirm the ultrasound images of cattle with reticular diaphragmatic hernia through the observation of anatomopathological lesions. However, Kumar & Saini (2011), Kumar et al (2017) confirmed the ultrasound diagnosis of RDH through exploratory laparotomy and the observations of these authors were similar to those observed in this study. Both in the exploratory laparotomy performed by Kumar & Saini (2011), Kumar et al (2017) and in the necropsy of the cattle in this study, a herniary ring in the diaphragm and herniated reticulum into the chest cavity were observed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings are also in agreement with the findings of Mohindroo et al, (2007). Kumar et al, (2017) reported that ultrasonography was effective in diagnosing diaphragmatic hernia by using the cranial thoracic approach especially if there is in case extensive herniation of reticulum. This approach is better than using the caudal thoracic approach.…”
Section: Treatment a N D Discussionsupporting
confidence: 91%
“…[ 22 ] made the center of the radiographic beam for radiography of the reticular region at the 8 th rib in cattle. This centering at the 8 th rib may be better for the complete visualization of the reticulum, but the part cranial to or at the diaphragm is compromised which otherwise may be required for the diagnosis of reticulodiaphragmatic hernia [ 16 ] or to detect an SMFB lying at the diaphragm. Multiple radiographic views were done in this study, to rule out all the possibilities to detect a foreign body on a radiograph.…”
Section: Discussionmentioning
confidence: 99%